VD_FINDINFO Faillite / 2014 / 14 vom 15. April 2014 - VD Tribunal cantonal (2014)
FAILLITE SANS POURSUITE PRÉALABLE, CRÉANCIER, QUALITÉ POUR POURSUIVRE, RECOUVREMENT | 131 al. 2 LP, 174 al. 1 LP, 190 al. 1 ch. 2 LP, 194 al. 1 LP